2007
DOI: 10.2134/agronj2006.0321
|View full text |Cite
|
Sign up to set email alerts
|

One‐Time Tillage of No‐Till Systems: Soil Physical Properties, Phosphorus Runoff, and Crop Yield

Abstract: Continuous no-till (NT) has numerous benefits, including improved soil aggregate stability in the surface soil and increased rate of water infiltration, but accumulation of soil P at the soil surface with NT can increase P concentration in runoff. We hypothesized that occasional one-time tillage of NT land, conducted once in 10 or more years, can reduce P runoff and improve crop yields without reducing soil aggregation or increasing runoff. Research was conducted in long-term NT fields under rainfed corn [Zea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 30 publications
2
22
3
Order By: Relevance
“…As part of a study to determine effects of occasional tillage on NT systems (García et al, 2007; Quincke et al, 2007), this research addressed the hypothesis that deep inversion tillage could be done with minimal short‐term loss of SOC. The objective was to determine the effect of different one‐time tillage operations on short‐term CO 2 losses, and on the mass and vertical distribution of total and labile SOC.…”
contrasting
confidence: 97%
“…As part of a study to determine effects of occasional tillage on NT systems (García et al, 2007; Quincke et al, 2007), this research addressed the hypothesis that deep inversion tillage could be done with minimal short‐term loss of SOC. The objective was to determine the effect of different one‐time tillage operations on short‐term CO 2 losses, and on the mass and vertical distribution of total and labile SOC.…”
contrasting
confidence: 97%
“…However, the increased bulk density under this treatment in our study was not in accord with Pierce et al (1994), who reported that periodical plowing decreased soil bulk density in the 0-15 cm depth. Also, the reduced water stable aggregates content in the occasional tillage field did not correspond with Quincke et al (2007b) who observed no effect of occasional tillage on this soil characteristic.…”
Section: Soil Physical Characteristicscontrasting
confidence: 75%
“…The mean sorptivity and transmissivity were somewhat higher in the no-till field, and the mean equilibrium infiltration rate and cumulative infiltration were significantly higher under this treatment (Fig 2). The decreased infiltration rate and sorptivity in the occasional tillage field only partially correspond with an eastern Nebraska study (Quincke et al, 2007b), where occasional tillage positively affected the water infiltration rate and negatively affected the soil water sorptivity. In another study site in eastern Nebraska, Quincke et al observed that occasional tillage reduced both infiltration rate and sorptivity.…”
Section: Surface Hydrologymentioning
confidence: 50%
“…The decreased surface soil Olsen P in the RotaT would have partially contributed to the reduced concentrations and loads of TDP and TP compared with the ConsT treatment. Similarly, Quincke et al (2007) reported that occasional one-time tillage of no-till systems effectively reduced dissolved P loss in runoff, particularly when concentrations of P in surface soil were high.…”
Section: Discussionmentioning
confidence: 93%